Процес неологізації лексичної системи сучасної англійської мови (на матеріалі найменувань особи) - Шиманович, Г.М. (Культура народов Причерноморья, 2014)
Стаття присвячена дослідженню значного за кількістю класу іменників – назв особи у
процесі неологізації словникового складу англійської мови наприкінці ХХ – початку ХХІ століть.
Когнітивна категорія «людина» в сучасній англійській мові охоплює величезний пласт лексики, яка
стосується опису людини в усіх її проявах. А також є свідченням того, що когнітивна та
лінгвокреативна діяльність людини має яскраво виражений егоцентричний характер. Значне збільшення
кількості назв особи у лексиці було зумовлено численними інноваціями в різних сферах життя і
діяльності, що виникали передусім в англомовних країнах і викликали необхідність концептуалізації
нового досвіду, категоризації нових знань людини. Наименования лица являються достаточно многочисленным классом существительных,
который заметно пополнился в английском языке в течение ХХ века и продолжает активно
поповняться и в ХХІ веке. Причинами стремительного роста этой группы существительных следует
считать разнообразие человеческой деятельности и поведения во всех проявлениях, что не могло не
привлечь внимания человека в рамках его лингвокреативной деятельности. Рост наименований лица в
лексической системе современного английского языка обусловлен также большим
словообразовательным потенциалом и гибкостью английского языка, а именно существованием
разнообразных моделей и способов словообразования, относительно свободным и быстрым переходом
частей отдельных слов в разряд словообразовательных формантов. The article is devoted to profound study of the process of coining neologisms in the Modern English
language. Nounsperson are very numerous nominative units in the lexical system of Modern English. Coinage of
these nominative units is caused by the numerous innovations in different spheres of life and people’s activity
that took place first of all in the English-speaking countries and were the reason of conceptualization of new
experience and categorization of new knowledge. The article tackles the influence of extralinguistic factors upon
development of English word-stock with the analyzed nominative units. Emphasis is laid on the ways and
mechanisms of this influence. Major models of word-formation and word-formative elements of Nounsperson are
analyzed against the background of extralinguistic factors. The process of coinage of numerous Nounsperson
during the XXth century and at the beginning of the XXI century is explained from the point of view of the great
word-formation potential of English and its flexibility, to be more exact, taking into consideration the existence
of different word-formative models and ways. Word-formation processes are closely connected with person’s
cognitive activity and stimulate verbalization of his intellectual activity, which, in its turn, is connected with
categorization and conceptualization of people’s experience.